Remodelling of microRNAs in colorectal cancer by hypoxia alters metabolism profiles and 5-fluorouracil resistance - Nijhuis, A; Thompson, H; Adam, J; Parker, A; Gammon, L; Lewis, A; Bundy, J; Soga, T; Jalaly, A; Propper, D; Jeffery, R; Suraweera, N; et al. (Oxford University Press, 2017)
Solid tumours have oxygen gradients and areas of near and almost total anoxia. Hypoxia reduces sensitivity to 5-fluorouracil (5-FU)-chemotherapy for colorectal cancer (CRC). MicroRNAs (miRNAs) are hypoxia sensors and were altered consistently in six CRC cell lines (colon cancer: DLD-1, HCT116 and HT29; rectal cancer: HT55, SW837 and VACO4S) maintained in hypoxia (1 and 0.2% oxygen) compared with normoxia (20.9%). CRC cell lines also showed altered amino acid metabolism in hypoxia and hypoxia-responsive miRNAs were predicted to target genes in four metabolism pathways: beta-alanine; valine, leucine, iso-leucine; aminoacyl-tRNA; and alanine, aspartate, glutamate. MiR-210 was increased in hypoxic areas of CRC tissues and hypoxia-responsive miR-21 and miR-30d, but not miR-210, were significantly increased in 5-FU resistant CRCs. Treatment with miR-21 and miR-30d antagonists sensitized hypoxic CRC cells to 5-FU. Our data highlight the complexity and tumour heterogeneity caused by hypoxia. MiR-210 as a hypoxic biomarker, and the targeting of miR-21 and miR-30d and/or the amino acid metabolism pathways may offer translational opportunities.